Near‐Earth heliospheric magnetic field intensity since 1750: 1. Sunspot and geomagnetic reconstructions. Issue 7 (14th July 2016) - Owens, M. J.; Cliver, E.; McCracken, K. G.; Beer, J.; Barnard, L.; Lockwood, M.; Rouillard, A.; Passos, D.; Riley, P.; Usoskin, I.; Wang, Y‐M.
Abstract: We present two separate time series of the near‐Earth heliospheric magnetic field strength ( B ) based on geomagnetic data and sunspot number (SSN). The geomagnetic‐based B series from 1845 to 2013 is a weighted composite of two series that employ the interdiurnal variability index; this series is highly correlated with in situ spacecraft measurements of B (correlation coefficient, r = 0.94; mean square error, MSE = 0.16 nT 2 ). The SSN‐based estimate of B, from 1750 to 2013, is a weighted composite of eight time series derived from two separate reconstruction methods applied to four different SSN time series, allowing determination of the uncertainty from both the underlying sunspot records and the B reconstruction methods. The SSN‐based composite is highly correlated with direct spacecraft measurements of B and with the composite geomagnetic B time series from 1845 to 2013 ( r = 0.91; MSE = 0.24 nT 2 ), demonstrating that B can accurately reconstructed by both geomagnetic and sunspot‐based methods. The composite sunspot and geomagnetic B time series, with uncertainties, are provided assupporting information . Key Points: The near‐Earth magnetic field intensity (B) can be reliably reconstructed back to 1750 Geomagnetic reconstructions of B provide the most accurate method of reconstructing B back to 1845 Uncertainty in the early sunspot record can be mitigated by using a composite approach to reconstructing B